Protective Effect of Low-molecular-weight Fucoidan on Lead-induced Oxidative Damage in HepG2 Cells Based on Cellular Metabolomics - Fan YU; Na LI; Yingying GUO; Xinyue DAI; Wenjia ZHU; Lin YAO; Yanhua JIANG; Lianzhu WANG (Shipin gongye ke-ji)
Objective: This study aimed to investigate the protective effects and metabolic regulatory mechanisms of low-molecular-weight fucoidan sulfate (F1) on lead (Pb)-induced oxidative damage in HepG2 cells. Methods: F1 was used as a test substance to establish an in vitro HepG2 cell model of Pb-induced injury with F1 intervention. Cell viability was assessed using the cell-counting kit-8 (CCK-8) assay. The levels of intracellular reactive oxygen species (ROS), glutathione (GSH), and malondialdehyde (MDA), as well as antioxidant enzyme activities were measured using biochemical methods. Apoptosis was detected using Annexin V-fluorescein isothiocyanate (FITC)/propidium iodide (PI) staining and flow cytometry. The high-concentration F1 group, which showed the best protective effect, was selected for intervention in Pb-induced HepG2 cells. Ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) was performed to detect intracellular endogenous metabolites, identify potential differential metabolites, and analyze related metabolic pathways. Results: Compared to the Pb model group, F1 treatment significantly alleviated the Pb-induced reduction in cell viability (P<0.05); markedly inhibited the increase in ROS and MDA levels (P<0.05); restored GSH content and the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT) (P<0.05); and reduced cell apoptosis (P<0.05). Metabolomic analysis revealed that F1 significantly regulated 17 potential differential metabolites (P<0.01), including glutamate, glutathione, and seleno-L-methionine. Enrichment analysis of key metabolites regulated by F1 indicated that F1 primarily influenced several metabolic pathways involved in redox functions, such as D-glutamine and D-glutamate metabolism; alanine, aspartate, and glutamate metabolism; selenium compound metabolism; and arginine biosynthesis. Conclusion: F1 exerts protective effects against Pb-induced oxidative damage in HepG2 cells, potentially through the regulation of amino acid metabolism and glutathione synthesis pathways.